Strategies For Protection Of Violence Against Children Through The Aisyiyah Love of Children (Gaca) Movement In Aba Branch Kindergarten, Mamajang, Makassar - Amirah, Amirah; Ulviani, Maria; Muthahharah, St (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
Children are the age group that needs guidance and teaching from adults. Furthermore, the growth and development of children must be protected from aspects of violence, especially "child predators", because children are a nation's asset towards progress and prosperity. This study aims to analyze the strategy for protecting violence against children through the Aisyiyah Cinta Anak (GACA) movement in Makassar City. This research is a qualitative research that aims to produce more powerful and in-depth data that can be obtained at the research location (field). This research was conducted in Mamajang District, Makassar. The results of the research are expected to find formulations of strategic concepts that can be implemented by Aisyiyah in protecting children from violence. The government provides the widest possible opportunity for the community to play a role in realizing child protection. The government continues to encourage the formation of community-based Integrated Child Protection in all regions, including Makassar City.